Does gender matter in doctor–patient communication during standard gynaecological consultations? An analysis using mixed methods. (14th October 2015) - Mazzi, Maria; Rimondini, Michela; Deveugele, Myriam; Zimmermann, Christa; Deledda, Giuseppe; Bensing, Jozien
Abstract : This paper assesses whether gender plays a role when male and female participants discuss the quality of doctor–patient communication in gynaecological consultations. A European multi-centre study was conducted comprising 259 participants in 35 gender- and country-specific focus groups. In all focus groups, a set of four videotaped Objective Structured Clinical Examination (OSCE) consultations was used as a prompt for discussion. The doctors' ability in communication was assessed by participants' ratings and by a quantified content analysis of their comments, using a mixed-method approach. Gender analysis was performed applying a set of generalized linear regression models. The findings indicated that gender differences were smaller than expected. The individual ratings of the overall quality of communication were similar for male and female participants, and there were hardly any differences in the content of the discussions. The only two exceptions were that female doctors were criticized more than male doctors when they made impersonal comments and that female participants were more outspoken than men, positively and negatively. The prevalence of gender similarities suggests that doctors' empathy, support, understanding and pleasantness are highly appreciated by both male and female participants and appear to transcend gender differences.